2001
DOI: 10.1046/j.1365-2982.2001.00265.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurotransmitter coding of enteric neurones in the submucous plexus is changed in non‐inflamed rectum of patients with Crohn’s disease

Abstract: Knowledge of the neurochemical coding of submucosal neurones in the human gut is important to assess neuronal changes under pathological conditions. We therefore investigated transmitter colocalization patterns in rectal submucosal neurones in normal tissue (n=11) and in noninflamed tissue of Crohn's disease (CD) patients (n=17). Neurone-specific enolase (NSE), choline acetyltransferase (ChAT), vasoactive intestinal polypeptide (VIP), substance P (SP), nitric oxide synthase (NOS) and calcitonin gene-related pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
113
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(122 citation statements)
references
References 40 publications
(50 reference statements)
9
113
0
Order By: Relevance
“…The proportion of neurons with a particular neurochemical code was in good agreement with a previous study (15), indicating that there was no experimental bias in that VSD may preferentially label a certain neuronal population. A potential problem is that the quality of the immunohistochemistry decreased with longer recording periods.…”
Section: Mapping the Human Enssupporting
confidence: 79%
“…The proportion of neurons with a particular neurochemical code was in good agreement with a previous study (15), indicating that there was no experimental bias in that VSD may preferentially label a certain neuronal population. A potential problem is that the quality of the immunohistochemistry decreased with longer recording periods.…”
Section: Mapping the Human Enssupporting
confidence: 79%
“…Homeostasis of these ions is compromised in inflammatory bowel disease (IBD), leading to motility dysfunctions, diarrhea and pain (1)(2)(3)(4). IBD includes ulcerative colitis (UC) and Crohn's disease (CD).…”
mentioning
confidence: 99%
“…The direct contact of luminal nutrients with L cells induces the second peak of GLP-2 secretion [65]. Over time it has been observed that patients with intestinal inflammation have changes in the pattern of encoding neurons [66,67] which may be signalled by a reduction in ongoing endogenous GLP-2. Therefore, it is priority to fully elucidate the release mechanism of native GLP-2 in order to optimize it.…”
Section: An Innovative Picture Of Glp-2mentioning
confidence: 99%